The effect of the China Connect - Chang Ma; John H. Rogers; Sili Zhou (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
We document the effect on Chinese firms of the Shanghai (Shenzhen)-Hong Kong Stock Connect. The Connect was an important capital account liberalization introduced in the mid-2010s. It created a channel for cross-border equity investments into a selected set of Chinese stocks while China's overall capital controls policy remained in place. Using a difference-in-difference approach, and with careful attention to sample selection issues, we find that mainland Chinese firm-level investment is negatively affected by contractionary U.S. monetary policy shocks and that firms in the Connect are more adversely affected than those outside of it. These effects are stronger for firms whose stock return has a higher covariance with the world market return and for firms relying more on external financing. We also find that firms in the Connect enjoy lower financing costs, invest more, and have higher profitability than unconnected firms. We discuss the implications of our results for the debate on capital controls and independence of Chinese monetary policy.
URN:NBN:fi:bof-202002041050
Keywords: F38; E40; E52; G15; 330; Capital Controls; Global Financial Cycle; Foreign Spillovers; FOMC Shocks; China Connect; Corporate Investment